SEBS as an Effective Nucleating Agent for Polystyrene Foams - Alberto Ballesteros (MDPI AG, 2021)
Different percentages of an elastomeric phase of styrene-ethylene-butylene-styrene (SEBS) were added to a polystyrene (PS) matrix to evaluate its nucleating effect in PS foams. It has been demonstrated that a minimum quantity of SEBS produces a high nucleation effect on the cellular materials that are produced. In particular, the results show that by adding 2% of SEBS, it is possible to reduce the cell size by 10 times while maintaining the density and open cell content of the foamed materials. The influence of this polymeric phase on the glass transition temperature (Tg) and the shear and extensional rheological properties has been studied to understand the foaming behavior. The results indicate a slight increase in the Tg and a decrease of the shear viscosity, extensional viscosity, and strain hardening coefficient as the percentage of SEBS increases. Consequently, an increase in the density and a deterioration of the cellular structure is detected for SEBS amounts higher than 3%.